IbM KELOMPOK USAHA CALON WIRAUSAHA PRODUK OLAHAN UBI JALAR BAGI KARANG TARUNA DESA BALE SARI & DESA BANJAR SARI. KEC. NGAJUM – KAB. MALANG - Nugroho Agus Santoso (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2016)
Program IbM is a community service to be performed in order to transfer the skills of production to prospective entrepreneurs Youth in order to be able to process materials sweet potatoes (Telo), Brownies Telo, Bak Pao Telo, Donat Telo & chips in order to take advantage of local produce that while this utilization is still very limited.After the young prospective entrepreneurs especially those belonging to the members of Youth is able to master the skills of production are good, they are expected to pioneer the independence of business / economy, to be able to improve their lives, besides that they are also able to create business opportunities for the local population, which temporarily The average dependent on the agricultural sector.When stub independence business / economy can already be controlled, then the necessary managerial skills include marketing aspects therein, so that they are able to distribute and diversify its products to consumers.